2020
DOI: 10.11604/pamj.2020.36.49.21098
|View full text |Cite
|
Sign up to set email alerts
|

Asthme et obésité: relation et implications thérapeutiques auprès des patients asthmatiques du Service de Pneumologie de Monastir, Tunisie

Abstract: Introduction L’obésité et l’asthme sont deux maladies chroniques touchant des millions d’individus à travers le monde. La présence d’un lien de causalité est suggérée. L'objectif de notre travail est d'étudier le profil de l’asthmatique obèse et de déterminer la relation entre les différents paramètres de sévérité de l’asthme avec les grades de l’obésité. Méthodes Il s'agit d'une étude rétrospective, monocentrique, analytique menée au Service de Pneumologie et d’Allergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…This suggests that obesity is strongly represented in severe asthma, regardless of the putative underlying pathobiology. Increased body fat leads to systemic inflammation and increased levels of adiponectin and leptin [124,126,127], which may skew towards a T2-low response [128,129], although T2-skewed inflammation is commonly still seen in obese asthma patients. Indeed, a recent analysis of the German Asthma Net registry suggested that among individuals with severe asthma, obesity was associated with higher symptom burden and significant differences in gastro-oesophageal reflux disease (GORD), anxiety and lung volumes, but not in T2 markers of disease (peripheral eosinophils, exhaled nitic oxide or IgE levels) [130].…”
Section: Obesitymentioning
confidence: 99%
“…This suggests that obesity is strongly represented in severe asthma, regardless of the putative underlying pathobiology. Increased body fat leads to systemic inflammation and increased levels of adiponectin and leptin [124,126,127], which may skew towards a T2-low response [128,129], although T2-skewed inflammation is commonly still seen in obese asthma patients. Indeed, a recent analysis of the German Asthma Net registry suggested that among individuals with severe asthma, obesity was associated with higher symptom burden and significant differences in gastro-oesophageal reflux disease (GORD), anxiety and lung volumes, but not in T2 markers of disease (peripheral eosinophils, exhaled nitic oxide or IgE levels) [130].…”
Section: Obesitymentioning
confidence: 99%